2021
DOI: 10.1177/14713012211048118
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative meta-synthesis of common and unique preferences for supportive services among persons with young onset dementia and their caregivers

Abstract: Background and Objectives Young onset dementias (young onset dementia) produce a myriad of stressors for persons with young onset dementia and their caregivers, yet there is a critical shortage of supportive services that address their needs. To develop such services, it is necessary to first comprehensively understand persons’ with young onset dementia and their caregivers’ service preferences. Therefore, we conducted a meta-synthesis to integrate and summarize qualitative data on persons’ with young onset de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Our study shows that younger people experience enhanced sense of agency not only when they are actively involved in disease management (Bannon et al, 2022) but also through public advocacy initiatives and cross-sector collaborations aiming to bring changes in real-life practice and public awareness of YOD.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Our study shows that younger people experience enhanced sense of agency not only when they are actively involved in disease management (Bannon et al, 2022) but also through public advocacy initiatives and cross-sector collaborations aiming to bring changes in real-life practice and public awareness of YOD.…”
Section: Discussionmentioning
confidence: 83%
“…Previous research has shown that maintaining autonomy is highly important for younger people (Greenwood and Smith, 2016). Bannon et al (2022) conducted a meta-synthesis of preferences for supportive services among younger people and their care-givers, and reported younger people's preference for services that enable managing symptoms while maintaining autonomy. Contrary to findings related to LOD (Holroyd et al, 2002), our study implies that younger people prefer to have honest facts about the condition and its prognosis to understand how to cope with symptoms and maintain control over their experience with YOD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, participants highlighted that it was pleasing to receive information tailored for different YOD-subtypes. Previous research has confirmed that caregivers have a need for YOD-subtype specific information ( Bannon et al, 2021 ; Bruinsma et al, 2021b ; Rosness et al, 2008 ). As known, support mainly focuses on Alzheimer's dementia or older peers ( Cations et al, 2017 ; Mayrhofer et al, 2018 ).…”
Section: Discussionmentioning
confidence: 94%
“…These results are consistent with the previous study on other versions of the RHAPSODY program ( Metcalfe et al, 2019 ). For YOD caregivers, flexibility is an important aspect of using support programs ( Bannon et al, 2021 ; Cations et al, 2017 ). This also applied to the RHAPSODY program which allowed participants to visit it from a place and time of their convenience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation